Systems Transformation and Multiple Pathways: Learning on CGIAR’s Ways of Working - Howard, Julie; Theuri, George (CGIAR Independent Advisory and Evaluation Service, 2025)
This summary of learning, prepared under the System Council–endorsed Multi-Year Evaluation Plan (MYEP), synthesizes evidence on two of CGIAR’s Ways of Working (WoWs) identified in the CGIAR 2030 Research and Innovation Strategy as priority approaches for CGIAR to do business differently, namely: